Pyruvate: Ferredoxin oxidoreductase is involved in IgA-related microbiota dysbiosis and intestinal inflammation - Wang, Kairuo; Guo, Yixuan; Liu, Yuanyuan; Cui, Xiao; Gu, Xiang; Li, Lixiang; Li, Yanqing; Li, Ming (Frontiers in Immunology, 2022)
Inflammatory bowel diseases (IBDs) are associated with both immune abnormalities and dysbiosis, characterized by a loss of Faecalibacterium prausnitzii (F. prausnitzii). However, the reason for F. prausnitzii deficiency remains unclear. The pattern of immunoglobulin A (IgA) coating of microbiota is altered in IBD. In this study, we identified an IgA-targeted protein in F. prausnitzii and investigated its relationship with microbiota dysbiosis and inflammation. 16S rDNA seque¬ncing and IgA enzyme-linked immunosorbent assay (ELISA) were applied to identify bacterial community and IgA changes in ulcerative colitis (UC) patients, which revealed that F. prausnitzii was underrepresented in UC patients with elevated F. prausnitzii-reactive IgA in the fecal supernatant. Forced immunization with F. prausnitzii in rabbits led to high interferon-γ (IFN-γ) transcription in the colon, along with beta diversity disturbance and intestinal inflammation. To screen for potential IgA-reactive proteins in F. prausnitzii lysates, we conducted western blotting and mass spectrometry analyses. Pyruvate: Ferredoxin Oxidoreductase (PFOR) was identified as an IgA-binding antigen of F. prausnitzii. After cloning and purification, PFOR immunoreactivity was validated in peripheral blood mononuclear cells (PBMCs), which showed elevated expression of inflammatory cytokines. Single-cell sequencing (scRNA-seq) revealed enhanced signals in both T regulatory cells (Tregs) and monocytes after PFOR incubation. Furthermore, phylogenetic analysis revealed that PFOR was a common but conserved protein among the gut bacteria. Our results collectively suggest that PFOR is a bioactive protein in the immune system and may contribute to host-microbial crosstalk. Conserved but bioactive microbial proteins, such as PFOR, warrant more attention in future host-microbial interaction studies.